An exergoeconomic assessment of waste heat recovery from a Gas Turbine-Modular Helium Reactor using two transcritical CO2 cycles. (15th October 2016) - Wang, Xurong; Dai, Yiping
Highlights: A Gas Turbine-Modular Helium Reactor is coupled with two transcritical CO2 cycles. Exergoeconomic analysis and optimization of the combined cycle was performed. The energy efficiency of the cogeneration system was enhanced by 7.92% at 850 °C. The overall exergoeconomic factor of the system could up to 55.2%. Abstract: A comprehensive study is performed on an energy conversion system which combines a gas turbine-modular helium reactor (GT-MHR) and two transcritical CO2 cycles (tCO2 ). The aim of this study is to assess the energy, exergy and economic behavior of the proposed system, considering five indicators: the energy efficiency, the exergy efficiency, the total exergy destruction cost rate, the overall exergoeconomic factor and the total cost rate. A parametric study is also conducted to evaluate the influence of key decision variables on the GT-MHR/tCO2 performance. Finally, the combined cycle is optimized to minimize the total cost rate. The results show that the energy efficiency of GT-MHR/tCO2 cycle is 7.92% higher than that of the simple GT-MHR cycle at 850 °C. The largest exergy destruction rate takes place in the reactor, and after that in the helium turbine and the recuperator. The components in tCO2 cycles have less exergy destruction. When the optimization is conducted based on the exergoeconomics, the overall exergoeconomic factor, the total cost rate and the total exergy destruction cost rate are 55.2%, 20, 752 /h and 9292 /h, respectively.